Development and characterization of sodium alginate based active edible films incorporated with essential oils of some medicinal plants - Mahcene, Z.; Khelil, A.; Hasni, S.; Akman,P. K.; Bozkurt, Fatih; Birech K.; Tornuk F. (Elsevier B.V., 2020)
The aim of this study was to develop sodium alginate based active films incorporated with essential oils (EO) of R. officinalis L, A. herba alba Asso, O. basilicum L and M. pulegium L. the films were characterized in terms of bioactive properties including thickness, moisture content, water vapor and oxygen permeability, release test, mechanical, molecular, biodegradability and thermal properties. The results showed that the active films had a strong antibacterial effect against the six pathogenic bacteria with the inhibition zone between18.5 and 38.67 mm. furthermore, the antioxidant capacity of the films ranged from 4.57% to 23.09%. According to results of release test, physical, molecular, mechanical, biodegradability, thermal and barrier properties, the EOs were uniformly dispersed in the polymer matrix and improved slightly thermal (Tm) and barrier properties, while decreased tensile strength and it was obtained that this film is biodegradable in the soil. In conclusion, it could be said that sodium alginate based edible films incorporated with EO have a potential to be used food packaging applications. © 2019 Elsevier B.V.
PubMed ID: 31843601
Keywords: Edible film; Essential oils; Sodium alginate